Inovasi Transportasi yang Kurang Inklusif Studi Kasus: Whoosh Kereta Cepat - Syarief, Ravi Azhar; R, Riswanda; Hanan, Arron Rizq (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article examines the Whoosh High-Speed Rail project as a form of public service innovation that is officially framed as a symbol of national progress and technological modernization. Behind this narrative, however, various structural issues reveal a significant gap between innovation claims and the actual quality of public service experienced by society. This study aims to analyze whether Whoosh represents a citizen-oriented public service innovation or merely a symbolic and elitist form of development. The research employs a literature review method by analyzing policy documents, academic publications, and relevant media reports related to the planning, financing, and implementation of the project. The analysis is guided by Mulgan and Albury’s public sector innovation framework, which emphasizes user orientation, public value creation, and sustainability. The findings indicate that Whoosh primarily reflects symbolic innovation, prioritizing political prestige and technological imagery over inclusive access and social equity. High ticket prices, weak intermodal integration, and fiscal risks demonstrate that this innovation deviates from the principles of public service as mandated by Law No. 25 of 2009 on Public Services.